Powder metallurgy of titanium II selected, peer reviewed papers from the 3rd Conference on Powder Processing, Consolidation and Metallurgy of Titanium, August 31 - September 3, 2015, Lüneburg, Germany - Ebel, Thomas; Pyczak, Florian (Key engineering materials ;, 2016)
This book gives a comprehensive overview on the technical and scientific status in the field of powder metallurgy of titanium and titanium alloys and points out the most important current research topics in this emerging area.